TINJAUAN KASUS PENCEMARAN NAMA BAIK BERDASARKAN KUHP YANG BERKEPASTIAN HUKUM - Angelina, Jennifer; Ratnawati, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Articles 310–316 of the Criminal Code address the offense of defamation of reputation, with the goal of safeguarding individuals' honor and dignity. The standards for what is considered damage to one's reputation require reevaluation with regard to numerous aspects. The public's hazy understanding of defamation further highlights the importance of having precise legal guidance. Reviewing pertinent statutes and court records is an integral part of the normative law research methodology. The ruling by the Constitutional Court in Decision No. 78/PUU-XXI/2023 states that the defamation Criminal Code Article 310 Paragraph 1 is deemed